Three new species of Pleurothallis (Orchidaceae: Pleurothallidinae) in subsection Macrophyllae-Fasciculatae from northern South America - Wilson, Mark (2016)
The history of the taxonomy of Pleurothallis R.Br. subsection Macrophyllae-Fasciculatae and recent descriptions in that group are summarized. The phylogenetic position of the group based on preliminary molecular data and the appropriateness of the proposed genera Acronia C.Presl. and Zosterophyllanthos Szlach. & Marg. for this group are discussed. Three new species from northern South America are described: Pleurothallis rubrifolia from southeastern Ecuador and northeastern Peru; Pleurothallis nangaritzae from southeastern Ecuador; and Pleurothallis castanea. Labellar micromorphology examined by scanning electron microscopy for P. rubrifolia and P. nangaritzae is discussed in relation to taxonomy and possible pollinator interactions.